Late age stages of Sobolewskia sibirica(Willd.) P.W.Ball (Brassicaceae), an endemic to the flora of Crimean Montains (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
In the big life cycle of Sobolewskia sibirica, a relict endemic to the flora of Crimean Montains, late generative stage and senile stage are absent in todays popoulations. Generative development of plants is limited by summer lack of the water. When growing ex situ in the Southern Coast of the Crimea, the plants show complete ontogenesis including senile age. The morphological characters of late age stages in S. sibiricaare revealed.
Keywords: the Crimea, Sobolewskia sibirica, relictual endemic, life form, ontogenesis.